SOLVERS OR THE MAGNIFICENT SEVEN OF MATHCAD - Elena P. Bogomolova; Valeriy F. Ochkov; Mati Heinloo (Открытое образование (Москва), 2016)
This article describes the basic mathematical tools of Mathcad that allow solving equations and systems of equations by analytical, numerical and graphical methods.